Employer’s Administrative Strategies as Correlates to Workers’ Job Performance - Esther, Eze Chidinma; Udoka, Eze Val Hyginus (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
This research study was carried out in public secondary schools in Obollo-Afor Education Zone of Enugu state to investigate principals’ administrative strategies as correlates of teachers’ job performance. This research study was guided by two research question and two formulated hypotheses whereas correlational survey design was adopted in the study. The population size of the study was 1854 which comprised of both the principals and teachers in selected 48 public secondary schools in Obollo-Afor education Zone of Enugu state, Nigeria. Proportionate stratified random sampling technique was used to obtain a sample size of 605 teachers for the study. This research was guided by two formulated research questions titled Principals’ Administrative Strategies Questionnaire (PASQ) and Teachers’ Job Performance Questionnaire (TJPQ) which were used as instrument for data collection. Cronbach Alpha method was used to obtain the internal consistency of the used instruments PASQ and TJPQ which yielded 0.73 and 0.72 respectively. Data collected were analyzed using regression analysis while regression ANOVA was used in testing the formulated hypotheses at 0.05 level of significance. The research result also showed that a high positive relationship exists between principals’ strategies in open communication and management of staff welfare and teachers’ job performance in Public secondary schools. This study among others recommended that principals in public secondary schools should adopt positive administrative strategies as identified in this study to promote teachers’ job performance.